NUMBER OF SPECIES, APPEARANCE AND BEHAVIOR OF DOLPHINS (DELPHINIDAE) IN SOLOR WATERS, EAST FLORES, EAST NUSA TENGGARA - Oldi Balo Rante; Omega Raya Simarangkir; Muhammad Iqbal Herwata Putra (Fakultas Perikanan dan Kelautan, Universitas Riau, 2021)
Research on dolphin populations in Solor waters is done in two stages through primary data collectionconducted in June until July 2017 and secondary data retrieval conducted in February 2018. The studyaims to know the total amount of species, species behavior, and sighting frequency of dolphins. Surveyswere conducted using a double platform boat. The survey successfully identified four dolphin speciesconsisting of Spinner dolphin (Stenella longirostris). Risso’s dolphin (Grampus griseus), Fraser’s dolphin(Lagenodelphis hosai), and Pantropical spotted dolphin (Stenella attenuata). The behavior of the dolphinsduring observation are feeding, travelling, and logging. Stenella longirostris is the most frequentlyobserved species with 632 sightings (91.33%) in June 2017 and 647 sightings (80.07%) in July 2017.